2020
DOI: 10.1002/ajmg.a.62030
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTSL2 gene variant in patients with features of autosomal dominant connective tissue disorders

Abstract: Ehlers‐Danlos syndrome (EDS) consists of a heterogeneous group of genetically inherited connective tissue disorders. A family with three affected members over two generations with features of Dermatosparaxic EDS (dEDS) autosomal dominant transmission was reported by Desai et al. and having a heterozygous nonsynonymous missense variant of ADAMTSL2 (c.1261G > A; p. Gly421Ser). Variation in this gene is also reported to cause autosomal recessive geleophysic dysplasia. We report five unrelated patients with the Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Here, we showed that stb / stb mice exhibited dwarfism with shortened longitudinal bones and thickened skin, which are consistent with the abnormalities caused by mutated ADSMTSL2 / Adamtsl2 genes in humans (Le Goff et al 2008 ; Piccolo et al 2019 ; Allali et al 2011 ; Steinle et al 2021 ), dogs (Bader et al 2010 ) and mice (Hubmacher et al 2015 ). In addition, the present histological analysis of the tibial growth plate revealed that stb / stb mice showed a remarkable reduction in the hypertrophic chondrocyte layer.…”
Section: Discussionsupporting
confidence: 79%
“…Here, we showed that stb / stb mice exhibited dwarfism with shortened longitudinal bones and thickened skin, which are consistent with the abnormalities caused by mutated ADSMTSL2 / Adamtsl2 genes in humans (Le Goff et al 2008 ; Piccolo et al 2019 ; Allali et al 2011 ; Steinle et al 2021 ), dogs (Bader et al 2010 ) and mice (Hubmacher et al 2015 ). In addition, the present histological analysis of the tibial growth plate revealed that stb / stb mice showed a remarkable reduction in the hypertrophic chondrocyte layer.…”
Section: Discussionsupporting
confidence: 79%
“…Fibrillin 1 is encoded by FBN1 , in which pathogenic variants underlie Marfan syndrome and ectopia lentis and have been reported for sporadic cases of SCAD . Paralogues of ADAMTSL4 , ADAMTSL6 ( alias of THSD4) , and ADAMTSL2 have been described in either aortic aneurysm, or probands with features of autosomal dominant connective tissue disorders, with similar functional roles to bind with fibrillin 1 and promote microfibril assembly . Combining evidence from unbiased GWAS, proband phenotypic correlation, functional roles in extracellular matrix microfibril formation, localization to the arterial tunica media vascular smooth muscle cells, support the consideration of ADAMTSL4 as a candidate gene for SCAD.…”
Section: Discussionmentioning
confidence: 99%
“…( 3 ) Furthermore, Steinle and colleagues described five unrelated individuals with dermatosparaxic Ehlers‐Danlos syndrome (dEDS) presenting with generalized joint hypermobility and fragility of the connective tissue caused by an autosomal dominant variant in ADAMTSL2 (c.1261G>A, p.(Gly421Ser)). ( 25 ) The contrasting clinical features of connective tissue laxity in dEDS versus tissue rigidity in GPHYSD1 and Al‐Gazali skeletal dysplasias suggests the possible gain‐of‐function effect of the p.(Gly421Ser) variant and thus further expands the spectrum of ADAMTSL2‐related disorders.…”
Section: Discussionmentioning
confidence: 99%